Anaisis Penggunaan Aplikasi LOS Terhadap Percepatan Aproval Kredit - Baginda Oloan Lubis; Budi Santoso - STMIK Nusa Mandiri; Achmad Maezar Bayu Aji; Ali Haidir; Agus Salim - UBSI (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2019)
Abstract - In the field of financing the LOS Application (Loan Origination System) is very helpful in daily activities and facilitates work so that jobs are easier, faster and more effective. The era of globalization has demanded that all information be accessed quickly and practically. The use of LOS applications becomes very important to support the process of business work activities in dealing with situations and conditions that are developing quickly. LOS application in general has been used by several banking institutions to support the work process. With the use of the LOS application in the corporate environment, credit analysts feel helped to facilitate the implementation of tasks and their work in processing data, calculating credit simulations and recording data from prospective customers. in this study is measuring the influence of the LOS Application on the acceleration of Credit Aproval in the corporate environment by processing the results of questionnaire data and analyzing the results of the study. The purpose of this test is to find out how strong the influence and magnitude of the contribution of the independent variable to the dependent variable which in this case is the LOS Application as the independent variable and the Credit Acceleration Acceleration as the dependent variable. Based on the results of a simple linear regression test, the value of tcount is 0.218 with a significance level of 0.066 with a table of 0.435. It means that the result has a very positive value from the respondent. So it can be decided that the research hypothesis (H1) which states